Experiences of a junior doctor during the COVID-19 pandemic when it all began - Sharma, Rajiv (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Challenges faced by a young doctor recently passed out from medical school and then into a seemingly neverending wave of the virus that left us breathless.